From capacity to performance: pathways of democratic resilience in Asia - Croissant, Aurel; Waldner, Niklas (Contemporary politics, 2025)
Despite the prominence of the resilience concept in democracy studies, attempts to actually measure democratic resilience, and to understand the causal pathways that link a political system’s capacity to remain or become resilient (‘resilience capacity’) to its actual degree of resilience (‘resilience performance’), remain rare. Using a fuzzy set Qualitative Comparative Analysis (fsQCA), this study examines the level of democratic resilience and the causal pathways through which capacities impact the resilience performance of 18 countries and 35 cases in Asia-Pacific in the context of two exogenously induced crises. We show that, despite the pessimistic mood in current democratisation studies, there is considerable variation in the resilience performance of electoral regimes in this region. Furthermore, we identify two equally sufficient combinations of causal conditions to explain democratic resilience and a single sufficient condition to explain weak or absent democratic resilience.